INOVASI METODE PEMBELAJARAN MONTASE SEBAGAI UPAYA PENGUATAN KAPASITAS KADER KESEHATAN DALAM PENGENDALIAN DAN PENCEGAHAN PENULARAN TBC - Linda Widyarani; Cecilya Kustanti (STIKes MERCUBAKTIJAYA, 2021)
Tuberculosis is an airborne disease caused by the bacterium mycobacterium tuberculosis, transmission occurs when a person inhales droplet nuclei containing mycobacterium tuberculosis, is spread from person to person through the air. The health cadres play an essential role for tuberculosis control and prevention. Therefore tuberculosis knowledge and skills among health cadres needs to be strengthened. Knowledge is a very important factor in shaping a person's actions, behaviors based on knowledge will last longer than those without it. This study aims to analyze and to prove the influence of education with montage learning methods in strengthening the role of health cadre in TB control and prevention. Used an pre experimental design and one group pre test and post test design with sampel of 20 people. Data collected using a questionnaires. Analysis used paired t-test with a significance level of 5% (α = 0,05). The result of the study provides that knowledge and skills of health cadres about TB control and prevention before intervention shows the lowest score of 58,75±14,59 and after intervention of 74,25±10,30. The results of the research used paired t-test showed that the cadres knowledge and skills about TB control and prevention rise after the montage learning methods, while the value of p value was 0,003 < 0,05.